Monitoring Norman, Oklahoma for temporal variation in SARS-CoV-2 using wastewater during University of Oklahoma football games - Rhodes, Emily (My University, 2022)
Coronavirus Disease 2019, more commonly referred to as COVID-19, is the disease caused by the virus Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). It is difficult to then get an accurate measure of cases through typical epidemiological methods such as clinical testing because many people do not know they have the disease. However, SARS-CoV-2 viral particles are often excreted by infected hosts, including those who are asymptomatic, and can be tracked through wastewater in a process called wastewater-based epidemiology (WBE). A problem that complicates WBE is that humans are not static and move in and out of sewer drainages throughout the day. One way to track human movement anonymously is through their cell phones and a software called StreetLight®. Football games at the University of Oklahoma provided an opportunity to combine WBE with StreetLight software to determine if there was an increase in the amount of SARS-CoV-2 in the wastewater due to large events. To determine this, wastewater samples were taken hourly at the City of Norman Water Reclamation Facility (NWRF) beginning on Saturday mornings and ending on Sunday mornings. To compare the amount of SARS-CoV-2 in the wastewater on gamedays was different than other days, composite samples were collected from the NWRF representing weekdays as well as two control Saturdays were selected to sample (one per football season). Finally, population data was collected at hourly intervals on Saturdays to normalize the SARS-CoV-2 concentrations, resulting in a measure we called the viral load per person and make the amount of SARS-CoV-2 in the wastewater comparable between seasons. This study can inform decision makers about hosting large-scale events throughout the rest of the pandemic, as well as during other disease outbreaks. Furthermore, the viral load per person is a novel way of presenting this data that makes comparing sewer drainages possible.
Keywords: SARS-CoV-2; Wastewater Based Epidemiology; Environmental Science; Biology, Microbiology.